2016
DOI: 10.1103/physrevb.94.144103
|View full text |Cite
|
Sign up to set email alerts
|

Theory of driven nonequilibrium critical phenomena

Abstract: A system driven in the vicinity of its critical point by varying a relevant field in an arbitrary function of time is a generic system that possesses a long relaxation time compared with the driving time scale and thus represents a large class of nonequilibrium systems. For such a manifestly nonlinear nonequilibrium strongly fluctuating system, we show that there exists universal nonequilibrium critical behavior that is well described incredibly by its equilibrium critical properties. A dynamic renormalization… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
60
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(60 citation statements)
references
References 128 publications
(183 reference statements)
0
60
0
Order By: Relevance
“…Besides the case of changing g, it has been shown that the dynamics of changing the symmetry-breaking field h as h = R h t + h 0 for a large h 0 also shows a scaling behavior [22,23,28,29,34]. In this case, h 0 is irrelevant.…”
Section: Effects Induced By the Initial Condition In The Kibble-zurekmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides the case of changing g, it has been shown that the dynamics of changing the symmetry-breaking field h as h = R h t + h 0 for a large h 0 also shows a scaling behavior [22,23,28,29,34]. In this case, h 0 is irrelevant.…”
Section: Effects Induced By the Initial Condition In The Kibble-zurekmentioning
confidence: 99%
“…In this case, h 0 is irrelevant. According to the FTS theory [28,29,34], the effective time scale induced by the external driving is ζ e ∼ R h −z/r h , in which r h = z + βδ/ν, with δ being defined as M ∼ h 1/δ at g = 0.…”
Section: Effects Induced By the Initial Condition In The Kibble-zurekmentioning
confidence: 99%
See 1 more Smart Citation
“…To go beyond KZM, it is important to investigate, both theoretically and experimentally, to what extent the scaling theory should be modified when the initial adiabaticity breaks down. For classical phase transitions, effects induced by a non-equilibrium initial state near the critical point have been studied 26,27 . However, the conclusion cannot be directly generalized to the real-time quantum critical dynamics, because the dynamical properties are The dash-dotted line (blue), which is exactly at the critical point and parallel with the vertical axis, is the starting state in the driven dynamics studied in Ref.…”
Section: Introductionmentioning
confidence: 99%
“…A candidate is finite-time scaling (FTS) through manipulating dynamics [52,53]. This is to change the parameter of a system through its critical point at a finite rate R. Similar to the instantaneous change of parameters in DLG, such kinds of driving can also lead to a series of driven nonequilibrium critical phenomena such as negative susceptibility and competition of various regimes and their crossovers, as well as violation of fluctuation-dissipation theorem and hysteresis [15]. FTS is the temporal correspondence to FSS.…”
mentioning
confidence: 99%